Improving the quality of neonatal health care in Ethiopia: a systematic review - Belay, Demeke Mesfin; Erku, Daniel; Bayih, Wubet Alebachew; Kassie, Yohannes Tesfahun; Minuye Birhane, Binyam; Assefa, Yibeltal (Frontiers in Medicine, 2024)
Background: Ensuring high-quality healthcare for newborns is essential for improving their chances of survival within Ethiopia's healthcare system. Although various intervention approaches have been implemented, neonatal mortality rates remain stable. Therefore, the present review seeks to identify initiatives for enhancing healthcare quality, their effects on neonatal well-being, and the factors hindering or supporting these Quality Improvement (QI) efforts' success in Ethiopia.: We searched for original research studies up to June 23, 2023, using PubMed/Medline, WHO-Global Health Library, Cochrane, Clinical Trials.gov, and Hinari. After selecting eligible studies, we assessed their quality using a mixed-method appraisal tool. Quality of care refers to how healthcare services effectively improve desired outcomes for individuals and patient populations. It encompasses vital principles such as safety, effectiveness, timeliness, efficiency, equity, and patient-centeredness. Results: We found 3,027 publication records and included 13 studies during our search. All these interventions primarily aimed to provide safe healthcare, with a strong focus on Domain One, which deals with the evidence-based routine upkeep and handling of complications, and Domain Seven, which revolves around ensuring staff competency, emerged as a frequent target for intervention. Many interventions aimed at improving quality also concentrate on essential quality measure elements such as processes, focusing on the activities that occur during care delivery, and quality planning, involving distributing resources, such as basic medicine and equipment, and improving infrastructure. Moreover, little about the facilitators and barriers to QIinterventions is investigated. Conclusions: This review highlights the significance of introducing QI initiatives in Ethiopia, enhancing the healthcare system's capabilities, engaging the community, offering financial incentives, and leveraging mobile health technologies. Implementing QI interventions in Ethiopia poses difficulties due to resource constraints, insufficient infrastructure, and medical equipment and supplies shortages. It necessitates persistent endeavors to improve neonatal care quality, involving ongoing training, infrastructure enhancement, the establishment of standardized protocols, and continuous outcome monitoring. These efforts are crucial to achieving the optimal outcomes for newborns and their families.